Halving poverty by 2015 - we can actually make it happen - Yunus, Muhammad (2003)
Looks at the effect of Bangladesh's Grameen Bank on that country's development. Argues that self-employment is the quickest and easiest way to create employment in Third World economies. Suggests that the goal of ending world poverty will be difficult to achieve while economic success is measured by personal financial gain rather the social gains. Notes that the Commonwealth could make a significant impact on the world by encouraging social investment through an expansion of financial services for the poor, and helping to meet the Millennium Development Goal of halving poverty by 2015.